2016
DOI: 10.1371/journal.pone.0164322
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Genome Editing via CRISPR in the Pathogen Cryptococcus neoformans

Abstract: Low rates of homologous integration have hindered molecular genetic studies in Cryptococcus neoformans over the past 20 years, and new tools that facilitate genome manipulation in this important pathogen are greatly needed. To this end, we have investigated the use of a Class 2 CRISPR system in C. neoformans (formerly C. neoformans var. grubii). We first expressed a derivative of the Streptococcus pyogenes Cas9 nuclease in C. neoformans, and showed that it has no effect on growth, production of virulence facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 55 publications
1
67
1
2
Order By: Relevance
“…It may be involved in the bacterial evolution, regulation of virulence gene expression, and the enhancement of pathogenicity (Hatoum‐Aslan & Marraffini, ). Particularly, in the pathogen, CRISPR is able to edit genome and modulate gene functions as an adaptive immune system (Arras et al., ; Sontheimer & Barrangou, ). Comparative analysis of the seven strain genomes (PR63039, CCUG10230, CCUG12901, CIP101113, CCUG12700, L41, and H1bi) showed that PR63039 genome contained three types of CRISPRs (Table S1); CCUG10230 genome contained four types of CRISPRs.…”
Section: Resultsmentioning
confidence: 99%
“…It may be involved in the bacterial evolution, regulation of virulence gene expression, and the enhancement of pathogenicity (Hatoum‐Aslan & Marraffini, ). Particularly, in the pathogen, CRISPR is able to edit genome and modulate gene functions as an adaptive immune system (Arras et al., ; Sontheimer & Barrangou, ). Comparative analysis of the seven strain genomes (PR63039, CCUG10230, CCUG12901, CIP101113, CCUG12700, L41, and H1bi) showed that PR63039 genome contained three types of CRISPRs (Table S1); CCUG10230 genome contained four types of CRISPRs.…”
Section: Resultsmentioning
confidence: 99%
“…The success of the CRISPR-Cas9 system for genome editing of S. cerevisiae led to many studies of the use of the system for genetic manipulation of various industrial or non-conventional yeasts [37][38][39][40]. Especially, Candida spp has attracted considerable interest because it contains several strains showing a significant potential for biotechnological use [41] and clinically important pathogen [42].…”
Section: Discussionmentioning
confidence: 99%
“…In C. neoformans , the expression of Cas9 was achieved by either integrating the Cas9 gene into the genome (Arras et al, ) or delivering it on a linear vector (Wang et al, ). In both cases, the gRNA was introduced into the cells on a linear vector.…”
Section: Crispr/cas9mentioning
confidence: 99%
“…Wang et al () showed that the efficiency of this system to generate nonsense mutations without the donor DNA was up to 80% and with the donor DNA ranged from 20 to 90%. Arras et al () showed that the HR events occur in this fungus with ~70% efficiency using the CRISPR/Cas9 system.…”
Section: Crispr/cas9mentioning
confidence: 99%